2014
DOI: 10.1111/rda.12384
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Angiotensin‐Converting Enzyme Increases Oestradiol Production in Ewes Submitted to Oestrous Synchronization Protocol

Abstract: This study aimed at evaluating the effects of angiotensin-converting enzyme inhibitor (enalapril) and angiotensin II antagonist (valsartan) on the oestradiol and progesterone production in ewes submitted to oestrous synchronization protocol. The animals were weighed and randomly divided into three groups (n = 7). A pre-experiment conducted to verify the effectiveness and toxicity of enalapril (0.5 mg/kg LW) and valsartan (2.2 mg/kg LW) showed that, in the doses used, these drugs were effective in reducing bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…One of the key points to explain these results may be the increase in the estradiol production through the inhibition of the ACE with the use of enalapril. In another study of our research group, we found results that show that enalapril, when used in a TAI protocol in sheep, led to an increase in estradiol on D12 of TAI protocol (Costa et al., ). In this case, the increase in estradiol occurred in the pre‐ovulatory period, in which a peak of estradiol occurs (Saifillizam, Routly, Smith, & Dobson, ) and which induces the peak of LH followed by ovulation (Moraes, Souza, & Gonçalves, ).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…One of the key points to explain these results may be the increase in the estradiol production through the inhibition of the ACE with the use of enalapril. In another study of our research group, we found results that show that enalapril, when used in a TAI protocol in sheep, led to an increase in estradiol on D12 of TAI protocol (Costa et al., ). In this case, the increase in estradiol occurred in the pre‐ovulatory period, in which a peak of estradiol occurs (Saifillizam, Routly, Smith, & Dobson, ) and which induces the peak of LH followed by ovulation (Moraes, Souza, & Gonçalves, ).…”
Section: Discussionmentioning
confidence: 75%
“…One of the key points to explain these results may be the increase in the estradiol production through the inhibition of the ACE with the use of enalapril. In another study of our research group, we found results that show that enalapril, when used in a TAI protocol in sheep, led to an increase in estradiol on D12 of TAI protocol (Costa et al, 2014).…”
Section: Discussionmentioning
confidence: 76%
“…Ovaries and follicles B-mode ultrasonography was performed each 24 h (each 12 h on the days of FSH/eCG administration); and used to measure all ovarian antral follicles. For measurement of structures of interest, including the growth pattern of the ovarian follicles, ultrasonographic examinations were recorded as videos, followed by the capture and measurement of images (with several different projections of ovary) using the Image J® software 7 , which was previously calibrated. The mean diameter (average of two dimensions, vertical and horizontal) of each identified follicle was taken from images.…”
Section: Ultrasound Examinationsmentioning
confidence: 99%
“…The settings of the scanner (Doppler sampling frequency (PRF) = 1.7 kHZ and color gain = 70% or just below the background noise level recorded in a motionless animal) remained constant for the duration of the study. Both arbitrary-scale [Absence (AB); Low (LO) and Moderate-high (MH) ( Figure 2) and quantitative analysis of the blood flow area (ImageJ ® ) 7 were used to assess the intraovarian blood flow in Doppler images, as described by Oliveira et al [24], with modifications. Briefly, in the images containing the cross-sectional area of the ovary with the strongest color Doppler signal, the ovary was out-lined manually and the total ovarian area (TA) recorded.…”
Section: Intraovarian Blood Flow and Doppler Velocimetric Parameters mentioning
confidence: 99%
See 1 more Smart Citation